1998
DOI: 10.1007/s002689900340
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pentastarch Solution in the Treatment of Patients with Hemorrhagic Hypovolemia: Randomized Phase II Study in the Emergency Room

Abstract: This study evaluates the hemodynamic effects of the administration of 10% pentastarch solution (PS) during the initial treatment of hypovolemia in trauma patients. This prospective randomized phase II study included trauma patients admitted to the emergency room with hemorrhagic hypovolemia: systolic blood pressure (SBP) < 90 mmHg. Upon admission, the patients were randomized to receive 10% PS (n = 12) or isotonic 0.9% NaCl solution (IS) (n = 11), infused intravenously in 250-ml boluses, repeated until SBP > 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Twenty-one trials were published in peer-reviewed journals, and 1 was published in abstract form 31. Twenty trials were reported in English-language journals,7,8,18,19,30-45 1 was in French46 and 1 was in German 47. Five trials were conducted in North America,19,30,40,42,44 16 in Europe7,8,18,31-39,41,43,46,47 and 1 in South America 45.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-one trials were published in peer-reviewed journals, and 1 was published in abstract form 31. Twenty trials were reported in English-language journals,7,8,18,19,30-45 1 was in French46 and 1 was in German 47. Five trials were conducted in North America,19,30,40,42,44 16 in Europe7,8,18,31-39,41,43,46,47 and 1 in South America 45.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty trials were reported in English-language journals,7,8,18,19,30-45 1 was in French46 and 1 was in German 47. Five trials were conducted in North America,19,30,40,42,44 16 in Europe7,8,18,31-39,41,43,46,47 and 1 in South America 45. Four trials received grant funding from manufacturers of HES,18,19,42,44 2 received government support,7,41 and 16 trials reported no funding source 8,30-40,43,45-47…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations